SALIM'S NEEDS IN DANNY BOYLE'S SLUMDOG MILLIONAIRE MOVIE: A HUMANISTIC APPROACH - DAROJATUN , FADLI (2006)
The major problem of the study is how are Salim's needs reflected in Danny Boyle's Slumdog Millionaire. The objectives of the study are to analyze the movie based on structural analysis and to analyze Salim's needs in Danny Boyle's Slumdog Millionaire based on Humanistic Approach. This study is literary study which can be categorized into descriptive qualitative study. The object of this study is Slumdog Millionaire movie by Danny Boyle. The data sources are primary data sources and secondary data sources, Slumdog Millionaire movie as the primary data and movie manuscript and articles from internet as secondary data. The method used for collecting the data is library research. The technique of data analysis is descriptive qualitative The result of the study is as follows. Firstly, it describes how Salim's needs reflected in Danny Boyle's Slumdog Millionaire. Secondly, the psychogical analysis shows that human will be motivated to attain his self-actualization after satisfying the lower needs (basic needs). Finally, a person will be motivated to develop of his potential.